An international year book of child care and protection : Being a record of state and voluntary effort for the welfare of the child, including information on marriage, divorce and illegitimacy, education, the care of the destitute child, treatment of juvenile delinquents and conditions of juvenile imployment throughout the world - Fuller, Edward; Alden, Percy; Save the children fund
Published for the Save the children fund.